2022
DOI: 10.1002/asia.202201078
|View full text |Cite
|
Sign up to set email alerts
|

A Green Route to Benzyl Phenyl Sulfide from Thioanisole and Benzyl Alcohol over Dual Functional Ionic Liquids

Abstract: Benzyl phenyl sulfide is a kind of important chemicals with wide usage, which is mainly prepared through a nucleophilic reaction of thiophenol with benzyl chlorides or benzyl alcohols, suffering from inherent drawbacks, such as low efficiency, requirements for equivalent acid or base catalysts and formation of harmful byproducts and waste. Herein, we report a green route to access various benzyl phenyl sulfide derivatives in good to excellent yields under mild conditions via the reaction of thioanisoles with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The metathesis of the C-S bond for the synthesis of more complicated homologs was only possible with transition metal catalysis that relies on ligand exchange with a second thiolate [15][16] or with the formation of a highly reactive aryne intermediate 32 or over an inoinc liquid. 33 To our delight, under the optimized reaction condition, simple aliphatic alcohols (4a-4d), alcohol bearing a phthalimide moiety (4e), and aromatic alcohols (4f-4h) can react with commercially available methyl phenyl thioether to give the alkyl transposition product, which is usually cumbersome to obtain with previous methods. A substrate scope study with 2-phenyl alcohol showed that various substituents, including alkyl (4i), electron-withdrawing (4j), electron-donating (4k), as well as halogens (4l-4p) on the aromatic thioethers are all well tolerated.…”
Section: Synthetic Scopementioning
confidence: 99%
See 1 more Smart Citation
“…The metathesis of the C-S bond for the synthesis of more complicated homologs was only possible with transition metal catalysis that relies on ligand exchange with a second thiolate [15][16] or with the formation of a highly reactive aryne intermediate 32 or over an inoinc liquid. 33 To our delight, under the optimized reaction condition, simple aliphatic alcohols (4a-4d), alcohol bearing a phthalimide moiety (4e), and aromatic alcohols (4f-4h) can react with commercially available methyl phenyl thioether to give the alkyl transposition product, which is usually cumbersome to obtain with previous methods. A substrate scope study with 2-phenyl alcohol showed that various substituents, including alkyl (4i), electron-withdrawing (4j), electron-donating (4k), as well as halogens (4l-4p) on the aromatic thioethers are all well tolerated.…”
Section: Synthetic Scopementioning
confidence: 99%
“…2). 33 Although 1a-2 and 1a-3 were not detected in the reaction mixture when 1a-2 was submitted to the standard reaction condition, a reduced yield of 3a was obtained and no 3a in the absence of ZnI 2 (Eq. 3), in contrast, 1a-3 gave higher a yield of 3a in the absence of ZnI 2 while its presence depressed the reaction (Eq.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%